Telemedicine use among patients with metastatic breast cancer during the COVID‐19 pandemic: Differences by race, age, and region. Issue 1 (4th October 2022) - Calip, Gregory S.; Cohen, Aaron; Rohrer, Rebecca; Wang, Xiaoliang; Wang, Xiaoyan; Webster, Amy; Wu, Amy; Griffith, Sandra D.; Showalter, Timothy N.; Miksad, Rebecca A.
Abstract: Purpose: Our objective was to describe differences in telemedicine use among women with metastatic breast cancer (mBC) by race, age, and geographic region. Methods: This was a retrospective cohort study of women with recurrent or de novo mBC treated in US community cancer practices that initiated a new line of therapy between March 2020 and February 2021. Multivariable modified Poisson regression models were used to calculate adjusted rate ratios (RR) and robust 95% confidence intervals (CI) associated with telemedicine visits within 90 days of therapy initiation. Results: Overall, among 3412 women with mBC, 751 (22%) patients had telemedicine visits following therapy initiation, with lower risks observed among older women (<50 years: 24%; 50–64 years: 22%; 65–74 years: 21%; ≥75 years: 20%). Greater telemedicine use was observed among Asian women (35%) compared to White (21%), Black (18%), and Hispanic (21%) women. Fewer telemedicine visits occurred in Southern (12%) and Midwestern (17%) states versus Northeastern (37%) or Western (36%) states. In multivariable models, women ages ≥75 years had significantly lower risks of telemedicine visits (RR = 0.76, 95% CI 0.62–0.95) compared to ages <50 years. Compared to patients in Northeastern states, women in Midwestern (RR = 0.46, 95% CI 0.37–0.57) and Southern (RR = 0.31, 95% CI 0.26–0.37) states had significantly lower risks of telemedicine visits; but not women in Western states (RR = 0.96, 95% CI 0.83–1.12). No statistically significant differences in telemedicine use were found between racial groups in overall multivariable models. Conclusions: In this study of community cancer practices, older mBC patients and those living in Southern and Midwestern states were less likely to have telemedicine visits. Preferences for communication and delivery of care may have implications for measurement of exposures and endpoints in pharmacoepidemiologic studies of cancer patients.